How to read church history ; v. 1 - Comby, Jean; Lydamore, Margaret; Bowden, John; Piorkowski, Liliane (London, UK SCM, 1985)
Contents : v. 1 : From the beginnings to the fifteenth century. Includes bibliographical references.
First published : Pour lire L'Histoire de L'Eglise Tome 1, Paris : Les Editions du Cerf, 1984
Keywords: Church history -- study and teaching